Dynamic response of ultra-high-performance concrete hollow beams under impact loading - Shen, Litao; Guo, Lu; Hou, Zebiao; Zhang, Tianhui (Frontiers in Materials, 2025)
The dynamic response of ultra-high-performance concrete (UHPC) hollow beams under drop-weight impact loading was investigated through a combined experimental and numerical simulation. High-speed cameras were utilized to record the dynamic response process of the UHPC hollow beams. The structural response process was categorized into four distinct phases: the initial peak loading phase, the steel fiber pull-out phase, the unloading phase, and the structural stabilization phase. A finite-element model developed in ABAQUS/Explicit accurately reproduced the experimental results and was employed to elucidate deformation and failure mechanisms. Further parametric studies revealed that the peak impact load increases with the height-to-width ratio under constant structural thickness. Beams with a height-to-width ratio of 1.4 exhibited stable post-peak load-bearing behavior. Moreover, for a fixed height-to-width ratio, configurations with greater thickness along the height and reduced thickness along the width demonstrated enhanced impact resistance. These findings provide valuable insights for the design of impact-resistant UHPC structures, highlighting the importance of geometric optimization to improve performance under dynamic loading conditions.